2008
DOI: 10.1245/s10434-007-9751-7
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA Exon 20 Mutation is Independently Associated with a Poor Prognosis in Breast Cancer Patients

Abstract: PIK3CA mutations are common in invasive ductal carcinomas of the breast. Our result suggests that PIK3CA exon 20 mutation is an independent risk factor for poor prognosis in breast cancer patients, indicating that differences in patient numbers with PIK3CA exon 20 mutations in study and control arms should be avoided in clinical trials of PI3K inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 15 publications
8
55
3
Order By: Relevance
“…Although similar findings have been reported in high-grade ovarian carcinomas, 25 reports have been contradictory regarding the prognostic significance of the PIK3CA helical and kinase domain mutations in breast carcinomas. [26][27][28][29] However, it has been reported that chickens injected with exon 20 PIK3CA mutants developed larger tumors than those injected with exon 9 PIK3CA mutants. 30 The distinct associations of the different PIK3CA mutations with histologic type, grade, and depth of myometrial invasion in endometrial carcinomas is consistent with the idea that different categories of mutants, defined by their structural and functional domains, would increase PI3K function by diverse mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar findings have been reported in high-grade ovarian carcinomas, 25 reports have been contradictory regarding the prognostic significance of the PIK3CA helical and kinase domain mutations in breast carcinomas. [26][27][28][29] However, it has been reported that chickens injected with exon 20 PIK3CA mutants developed larger tumors than those injected with exon 9 PIK3CA mutants. 30 The distinct associations of the different PIK3CA mutations with histologic type, grade, and depth of myometrial invasion in endometrial carcinomas is consistent with the idea that different categories of mutants, defined by their structural and functional domains, would increase PI3K function by diverse mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated a better overall survival (OS) and disease free survival (DFS) in breast cancer patients with PI3KCA mutations when compared with that of breast cancer patients without these mutations (Maruyama, 2007;Stemke-Hale et al, 2008;Kalinsky et al, 2009;Dupont, 2011). However, others showed that PI3KCA mutations in breast cancer patients are associated with poor clinical outcome (Li, 2006;Barbareschi et al, 2007;Lai et al, 2008). Our aim of this study is to identify mutational status of the two hotspot regions of PIK3CA (exons 9 and 20) in breast cancer.…”
Section: Phosphatidylinositol 3-kinase (Pi3kca) Oncogene Mutation Anamentioning
confidence: 99%
“…Since then, more than 1,500 PIK3CA mutations in diverse tumor types have been discovered (6). The most common mutant is His1047Arg (6), and mutations at this residue in breast and uterine cancers are associated with clinical prognosis (7)(8)(9). Biochemical assays have demonstrated that the His1047Arg mutant has a 2-fold increase in lipid kinase activity (10), that its activity increases further upon phosphopeptide binding (10), and that the activity is independent of Ras binding but dependent on p85 binding (11).…”
mentioning
confidence: 99%